ADSORPTION OF 4-CHLORPHENOL BY BROWN COAL ACTIVATED BY POTASSIUM HYDROXIDE - Tamarkina, Yuliia; Kucherenko, Volodymyr; Frolova, Iryna (WATER AND WATER PURIFICATION TECHNOLOGIES. SCIENTIFIC AND TECHNICAL NEWS, 2021)
The purpose of work is to evaluate the 4-chlorophenol (CP) adsorption capacity of brown coal activated carbons (ACs) prepared at different temperature of KOH activation. ACs were obtained in three stages: 1) impregnation of coal with a KOH solution, 2) heating (4 deg/min) in argon to a given temperature t (400-800°C) and exposure for 1 h, 3) cooling, washing from KOH, drying. The samples are designated as AC(t). Based on the N2 adsorption-desorption isotherms, the ACs total pore volume (Vt, cm3/g) and specific surface area (S, m2/g) were determined. The ACs adsorption capacity were measured at 25°С, CP concentration ≤700 mg/L, АC dosage – 1 g/L. The alkaline activation temperature was found to be a key factor in forming porosity of ACs and ability to adsorb CP. The CP maximum capacity (ACP(m), mg/g) increases 6.6 times up to 307 mg/g for AC(800) having S=1142 m2/g. The specific adsorption capacity (ACP(S) = ACP(m)/S, mg/m2) sharply decreases in a sample range from AC(400) to AC(550) and weakly depends on temperature at 550-800°C. The kinetics of CP adsorption is best described by a pseudo-second order model. The rate determining stage is the interaction of CP molecules with AC surface. The CP adsorption isotherms are best described by the Langmuir model. The dependence of the ACP(m) from S can be approximated by three linear equations that probably correspond to the three regions of forming surface adsorbtion centers (AdCs). The first (S≤370 m2/g) is characterized by a small adsorption capacity increment (kS=0.103 mg/m2), but a significant (16.4 times) decrease in the specific capacity ACP(S). In the second region (S=370-770 m2/g, t=550-750°C), capacity increment is 10 times more (kS=0.985 mg/m2) and in the third region (S≥770 m2/g, t≥750°C) the increase in CP capacity is the smallest (kS=0.067 mg/m2). The thermoinitiated formation of AdCs is assumed to be not proportional to the increase in surface area, and their chemical structure and reactivity is determined by the alkaline activation temperature.